Heparan Sulfate Structure Affects Autophagy, Lifespan, Responses to Oxidative Stress, and Cell Degeneration in Drosophila parkin Mutants. Issue 1 (1st January 2020) - Reynolds-Peterson, Claire; Xu, Jie; Zhao, Na; Cruse, Casey; Yonel, Brandon; Trasorras, Claire; Toyoda, Hidenao; Kinoshita-Toyoda, Akiko; Dobson, Jennifer; Schultheis, Nicholas; Jiang, Mei; Selleck, Scott
Abstract: Autophagy is a catabolic process that provides cells with energy and molecular building blocks during nutritional stress. Autophagy also removes misfolded proteins and damaged organelles, a critical mechanism for cellular repair. Earlier work demonstrated that heparan sulfate proteoglycans, an abundant class of carbohydrate-modified proteins found on cell surfaces and in the extracellular matrix, suppress basal levels of autophagy in several cell types during development in Drosophila melanogaster . In studies reported here, we examined the capacity of heparan sulfate synthesis to influence events affected by autophagy, including lifespan, resistance to reactive oxygen species (ROS) stress, and accumulation of ubiquitin-modified proteins in the brain. Compromising heparan sulfate synthesis increased autophagy-dependent processes, evident by extended lifespan, increased resistance to ROS, and reduced accumulation of ubiquitin-modified proteins in the brains of ROS exposed adults. The capacity of altering heparan sulfate biosynthesis to protect cells from injury was also evaluated in two different models of neurodegeneration, overexpression of Presenilin and parkin mutants. Presenilin overexpression in the retina produces cell loss, and compromising heparan sulfate biosynthesis rescued retinal patterning and size abnormalities in these animals. parkin is the fly homolog of human PARK2, one of the genes responsible for juvenile onset Parkinson's Disease. Parkin is involved in mitochondrial surveillance and compromising parkin function results in degeneration of both flight muscle and dopaminergic neurons in Drosophila . Altering heparan sulfate biosynthesis suppressed flight muscle degeneration and mitochondrial dysmorphology, indicating that activation of autophagy-mediated removal of mitochondria (mitophagy) is potentiated in these animals. These findings provide in vivo evidence that altering the levels of heparan sulfate synthesis activates autophagy and can provide protection from a variety of cellular stressors.